2019
DOI: 10.1029/2019wr025222
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Suspended Sediment in a Typical Alpine Alluvial River Reach: Insight From a Seasonal Survey

Abstract: The transport of suspended sediment is associated with important social, economic, and environmental issues. It is still unclear, however, how suspended sediments eroded on hillslopes are transferred downstream through the river system. In this study, we aimed to investigate this process by applying a sediment budget approach to a typical 3.5-km-long Alpine braided reach. Using high-frequency suspended load measurements combined with Monte Carlo simulations for uncertainty propagation, we observed a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…At 30 and 50 Hz, a clear change in scaling power occurs as discharge exceeds a value (11.9 m 3 /s) that corresponds to the modeled threshold of full particle mobility (Figure 8b, 8c) and can be related to pavement breakup in the braided reach as observed here by Misset et al (2019). For discharges higher than this critical value, the power‐law trend is steeper with an exponent of 4.4 at 30 Hz and 5.3 for 50 Hz.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…At 30 and 50 Hz, a clear change in scaling power occurs as discharge exceeds a value (11.9 m 3 /s) that corresponds to the modeled threshold of full particle mobility (Figure 8b, 8c) and can be related to pavement breakup in the braided reach as observed here by Misset et al (2019). For discharges higher than this critical value, the power‐law trend is steeper with an exponent of 4.4 at 30 Hz and 5.3 for 50 Hz.…”
Section: Resultssupporting
confidence: 75%
“…We studied a braided river reach approximately 600 m long and up to 90 m wide (Figure 1) that lies at an elevation of just above 1,000 m a.s.l., near the village of Villar‐Loubière. The riverbed has a gentle gradient of ~1% and is largely composed of gravel at the surface and includes finer material in the subsurface (Misset et al, 2019). The particle‐size distribution of the riverbed in the braided reach was determined by Misset et al (2020) and is shown in Figure 2.…”
Section: Study Area and Data Availabilitymentioning
confidence: 99%
“…The observed suspension‐gravel bed interactions are consistent with several flume and scarce field results. Previous studies show that fine particles infiltrate in the gravel matrix even for very low Rouse numbers and stay in the subsurface until the surface coarse bed particles are mobilized (Diplas, 1994; Frostick et al., 1984; Krishnappan & Engel, 2006), so that a relationship between suspended load and bedload is observed in gravel bedded streams (Meunier et al., 2006; Misset, Recking, Legout, Valsangkar, et al., 2019; Misset, Recking, Navratil, et al., 2019; Park & Hunt, 2017; Turowski et al., 2010). Also, in addition to the strong relationship between turbidity and seismicity, a weak relationship during the summer periods, when most high turbidity peaks occur, provides an indication of the origin of suspended sediment ( bed related vs. hillslope related ).…”
Section: Discussionmentioning
confidence: 99%
“…The finest fraction of fine sediments stored in the bed matrix (obtained using a resuspension technique detailed in Misset, Recking, Legout, Valsangkar, et al. 2019) was found to have a GSD range similar to surface deposits and sampled suspended particles.…”
Section: Field Site and Methodsmentioning
confidence: 99%
“…It remains however very difficult to estimate the total amount of fine sediment stock on gravel bars since these sediments are easily washed out and can also infiltrate into the gravel matrix. Indeed, it often represents a nonnegligible part of the sediment flux passing through the system (Misset et al, 2019). Moreover, very different dynamics can be observed from one class of sediments to another, i.e.…”
Section: Introductionmentioning
confidence: 99%